STUDENTS’ OPINION ON ONLINE LEARNING IN THE MIDST OF THE COVID-19 PANDEMIC - Hapsah Munajah; Chaidir Syahri (PROJECT (Professional Journal of English Education), 2022)
The objective of the study is to reveal the students’ opinion on online learning in the midst of the covid-19 plague. The covid-19 is a kind of virus that attack a human with fever, shortness of breath, influenza, and other types of pain in the same time. The covid-19 pandemic occurred in early December 2019 in Wuhan China. The pandemic spread throughout the world including Indonesia. Indonesia has more than 8000 people who have possitive covid-19. Because of that, Indonesian goverment give policy to push the number of victims. The policy is about Social distancing, restrictions on work activities, PSBB (Pembatasan social Berskala Besar), and termination of teaching and learning activities. The researcher uses qualitative method to get a deep data. The research define the result briefly. The researcher takes ten partisipants randomly. The twenty participants are the students of English education study programs. It can be concluded that students who are doing online learning in the midst of the covid-19 plague have  trouble from some reasons. In the other side, some of them have really good experiences with online learning. It is becaused they have time with their own family while they are struggling with their study. Keywords:  Online Learning, ICT, Covid-19, Students’ Opinion